Variability and Heritability Studies for Horticultural Traits in Ridge Gourd [Luffa acutangula (L.) Roxb.] - S., Harshitha; Sood, Meenakshi; K. M, Indiresh (International Journal of Bio-resource and Stress Management, 2019)
Ridge gourd is an important cucurbit cultivated in the tropical and sub-tropical regions of India as well as other parts of the world, especially for its green long fruits, consumed as vegetable. Genetic variability and penetrance of favourable characters to the progenies are two important factors in the success of any crop improvement programme. Therefore the present study was conducted with 25 genotypes of ridge gourd collected from different sources and their evaluation for growth parameters, fruit yield and yield contributing traits using Randomized Block Design at College of Horticulture, Mysuru, Karnataka during Kharif, 2015. The results indicated significant variability among the genotypes studied for all traits observed except for seed test weight. Considerable variability was found for fruit yield per plant (0.297 kg -1.83 Kg), with IC-92638 and ArkaSujath being the highest yielders. Number of fruits per plant varied from 1.60 (Ghataprabha Local) to 8.0 (IC-92638). High values of Phenotypic co-efficient (PCV) and genotypic co-efficient (GCV) of variation were observed for fruit yield per plant, number of fruits per plant, vine length and for seed yield per plant. These traits also exhibited high heritability coupled with high values of genetic advance expressed over per cent of mean, suggesting the possibility of improvement in these traits through simple selections. However, the earliness traits viz., days to 50% female flowering, days to first harvest, and fruit size in terms of length and fruit diameter exhibited moderate values of GCV and PCV along with moderate levels of heritability and genetics advance.